Low back pain and other overuse injuries in a group of Japanese triathletes - Manninen, J. S.; Kallinen, M. (British Journal of Sports Medicine, 1996)
OBJECTIVE: To document the incidence of low back pain and other overuse injuries in a group of triathletes, and to investigate any associations with various physical and triathlon related factors. METHODS: By means of a questionnaire, the physical characteristics, training habits, and the incidences of overuse injuries of 92 Japanese triathletes (70 males, 22 females) were documented. Student's t and chi 2 tests were used to determine the significance of any associations with injury incidence, as well as differences between subjects experiencing or not experiencing low back pain in the previous year. RESULTS: Low back pain was experienced by 32% of subjects in the previous year. The majority (54%) of low back pain episodes lasted under seven days, suggesting mainly soft tissue involvement, and 19% lasted over three months, suggesting involvement of the intervertebral discs. Weekly trunk flexor muscle training frequency was significantly greater (P = 0.035) for the low back pain subjects. Close to significant differences for average weekly cycling time, trunk flexor muscle training time, and low intensity aerobic training, as well near significant associations for weight training and average weekly triathlon training load, were also found. No other factors were significantly associated with low back pain. Low back injuries accounted for 28% of all injuries. Only the knee was a more common single site of injury (33%). CONCLUSIONS: The three most common injuries suffered by the triathletes were of the knee, back and shoulder. The low back pain suffered by many triathletes could be of a potentially serious nature. It is suggested that cycling is a major risk factor for low back pain in triathletes.